2010
DOI: 10.1002/pros.21163
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ack1 tyrosine kinase inhibitor on ligand‐independent androgen receptor activity

Abstract: Background Androgen receptor (AR) plays a critical role in the progression of both androgen-dependent and androgen-independent prostate cancer (AIPC). Ligand-independent activation of AR in AIPC or castration resistant prostate cancer (CRPC) is often associated with poor prognosis. Recently, tyrosine kinase Ack1 has been shown to regulate AR activity by phosphorylating it at tyrosine 267 and this event was shown to be critical for AIPC growth. However, whether a small molecule inhibitor that can mitigate Ack1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
117
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 84 publications
(123 citation statements)
references
References 30 publications
4
117
1
Order By: Relevance
“…ACK1, an intracellular tyrosine kinase, is considered to be implicated in regulating multiple aspects of tumor progression (13,16). Several studies have indicated that ACK1 overexpression is commonly observed in human cancers including lung and prostate cancer (27,33). Furthermore, it has been demonstrated that ACK1 can promote tumor growth via regulating pro-survival molecules such as AKT and AR in various cancers (26,31,33).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…ACK1, an intracellular tyrosine kinase, is considered to be implicated in regulating multiple aspects of tumor progression (13,16). Several studies have indicated that ACK1 overexpression is commonly observed in human cancers including lung and prostate cancer (27,33). Furthermore, it has been demonstrated that ACK1 can promote tumor growth via regulating pro-survival molecules such as AKT and AR in various cancers (26,31,33).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have indicated that ACK1 overexpression is commonly observed in human cancers including lung and prostate cancer (27,33). Furthermore, it has been demonstrated that ACK1 can promote tumor growth via regulating pro-survival molecules such as AKT and AR in various cancers (26,31,33). The role of ACK1 have been investigated in multiple tumor types (31,33).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EGF and Gas6 can also result in Tyr267 phosphorylation (Liu et al 2010b). Anti-androgens have no effect on tyrosine phosphorylation at 267 (Mahajan et al 2010); however, inhibition can be achieved using Dasatinib, a Src and Ack1 inhibitor (Liu et al 2010b). The AR isoform, AR8, has recently been identified.…”
Section: Tyrosine Phosphorylationmentioning
confidence: 99%
“…Ack1 has been reported to either promote clathrin-mediated endocytosis of EGFR and target it for degradation (23,24) or, conversely, to stabilize cell surface expression of EGFR (25), suggesting different functions for Ack1 in different cell types. Ack1 has also been reported to regulate the receptor tyrosine kinase Axl and the androgen receptor (22,26) and to interact with a number of molecules involved in vesicular trafficking, including clathrin, AP2 (adaptor protein 2), and SNX9 (sorting nexin 9) (27)(28)(29).…”
mentioning
confidence: 99%